Clinical and Non-Clinical Complaints Towards a Mental Health Service in the West of Ireland Over a Seven-Year Period - Andrew O'Malley; Elaine Walsh (BJPsych Open, 2024)
Aims To examine whether the rate of clinical and non-clinical complaints towards a mental health service (MHS) in the west of Ireland has changed over the preceding seven years. We aim to clarify the pathways for managing clinical and non-clinical complaints locally and compare with other MHS nationally. We aim to capture the nature of complaints, potential factors in any change in rate and quantify associated workloads via survey of senior clinicians involved in managing complaints.